Photosynthetic responses to water deficit in six Mediterranean sclerophyll species: possible factors explaining the declining distribution of Rhamnus ludovici-salvatoris, an endemic Balearic species. (Tree Physiology, 2002)
We sought to explain the declining distribution in the Balearic Islands of the endemic shrub Rhamnus ludovici-salvatoris R. Chodat, by comparing its photosynthetic response to drought with that of several widely distributed, competing Mediterranean species (R. alaternus L., Quercus ilex L., Pistacia lentiscus L., Q. humilis Mill. and P. terebinthus L.). [ABSTRACT FROM PUBLISHER]